EVALUATION OF THE IMPLEMENTATION OF URRICULUM FOR TEACHING ELEMENTARY SCHOOL MALAY LANGUAGE SKILLS TO MALAY LANGUAGE TEACHER STUDENTS AT THE TEACHER EDUCATION INSTITUTE (IPG) - Amat Tarop bin Sumo (Journal Civics And Social Studies, 2023)
This study aims to evaluate the Primary School Malay Language Skills Teaching curriculum among core Malay elective teacher students at IPG for the Bachelor of Teaching Degree Program (PISMP). This study will evaluate the effectiveness of this curriculum for non-option teacher students who take the Malay core elective as a minor subject. Stufflebeam's 1971 Evaluation Model which is Context- Input-Process-Product (CIPP) was used in this study. The effectiveness of this curriculum for student teachers will be seen in the dimensions of context, input, process and product. Quantitative methods using questionnaire surveys were used to obtain data from student teachers. Quantitative data was obtained through a questionnaire from 119 student teachers. Data analysis using IBM SPSS software version 26.0. Descriptive findings show that some aspects of context, input, process and product are good. Through this study it was found that the Primary School Malay Language Skills Teaching curriculum had a very positive effect on student teachers based on all four dimensions Aspects such as learning outcomes and curriculum content, physical resources, human resources, and assessment were found to have a positive effect on student teachers who take the course. The effectiveness of this curriculum for elective core Malay language teacher students is a catalyst to produce student teachers who have extensive knowledge about Primary School Malay Language Skills.